Things you save in a fire - Center, Katherine (New York : St. Martin's Press, 2019)
"Cassie Hanwell was born for emergencies. As one of the only female firefighters in her Texas firehouse, she's seen her fair share of them, and she's a total pro at other people's tragedies. But when her estranged and ailing mother asks her to give up her whole life and move to Boston, Cassie suddenly has an emergency of her own."--
"A novel" -- Cover.
Keywords: Women fire fighters -- Fiction; Fire fighters -- Fiction; Mothers and daughters -- Fiction; Fire stations -- Massachusetts -- Boston -- Fiction; Adult children of aging parents -- Fiction; Boston (Mass.) -- Fiction; Romance fiction